Silver Nanoparticles’ Biosynthesis and Characterization with the Extract of Jatropha curcas Leaf: Analysis of Corrosion Inhibition Activity - Kayode, Talabi Henry; Yetunde, Talabi Justina; Omotayo, Adewuyi Benjamin (UI Scholars Hub, 2022)
The plant-mediated nanoparticles synthesis process is gaining popularity because of its effective cost, eco-friendliness, and nontoxic nature. The current study presents the silver nanoparticles (AgNPs) which synthesized with AgNO3 as precursor salt and Jatropha curcas leaf extract. J. curcas leaf extract has phytochemicals that could reduce the precursor metal salt to nanoparticles and act as a capping agent surround the nanoparticles to enhance its stability. Phytochemical screening on J. curcas leaf extract showed that alkaloids, saponins, tannins, flavanoids, steroids, philobatannins, phenols, and cardiac glycosides are contained in the sample. The biosynthesized nanoparticles were investigated by UV-visible (UV-vis) spectroscopy, X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). UV-vis spectroscopy confirmed the fabrication of AgNPs at 250–400 nm. The solutions’ change of color from pale yellow to reddish brown indicated that AgNPs is formed. XRD analysis revealed that the synthesized AgNPs average crystal size was 36.4 nm. FTIR analysis indicated that the organic residues covered the nanoparticles. The inhibitory properties of the solution of the synthesized nanoparticles and the bulk extract were evaluated using medium carbon steel. The solution of the synthesized nanoparticles (10 ml) showed better corrosion inhibition efficiency of 87.10 % compared with the bulk extract.